The Influence of Investigative Audit and Whistleblowing System Implementation on The Prevention of Misuse of School Operational Aid Funds (Empirical Study at Jawa Barat BPKP Head Office) - Indriana Damaianti (Jurnal Mantik, 2020)
This study aims to analyze the influence of Investigative Audit and Whistleblowing System Implementation on the Prevention of Misuse of School Operational Aid Funds at BPKP Jawa Barat Head Office. The data collection method is done by sending a research questionnaire contained in the google form link. The population in this study were 83 auditors in the Deputy for Investigation who were still actively working. This research method uses descriptive statistics. The instrument test technique used includes validity and reliability tests. Classical assumption test which includes normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing which includes multiple linear regression test, F statistic test, t statistic test and determination coefficient test. Assisted testing using SPSS version 25. The results of this study indicate that the investigative audit has no effect on preventing operational assistance funds and the whistleblowing system has an effect on preventing operational assistance funds.